Removal of heavy metals from industrial wastewater using activated carbon - Nor Shahirah, Mohd Nasir (2010)
The presence of heavy metals in wastewater is known to cause severe damage to aquatic life, beside the fact that these metals kill microorganism during biological treatment of wastewater with a consequent time delay of the treatment process. Chromium is one of the major heavy metals present in wastewater which has toxic effect and is a strong oxidizing agent capable of being absorbed through the skin. Palm oil mills in Malaysia produce about 4.3 million tones of shell and the significant problems in the palm fruit processing is managing the wastes generated during the process. The palm shell can be converted into useful products such as activated carbon. So, this method will reduce industrial wastewater problem and will bring benefits to society. Hence, this research aims to use activated carbon produced from palm shell to remove Chromium from industrial wastewater. Pyrolysis was applied for the preparation of activated carbon from palm shell using furnace at 600ºC. The treatment of activated carbon was carried out by oxidizing it with sulphuric acid and coating with chitosan. Two adsorbents namely Palm Shell Activated Carbon (PSAC) and Palm Shell Activated Carbon coated with Chitosan (PSACC) were used to remove chromium from aqueous solution. The effects of pH of the solution, adsorbent dosage, agitation speed, and contact time on adsorption of chromium were studied. The experimental results proved that the chromium removal efficiency of PSACC was better compared PSAC. Freundlich and Langmuir isotherms were used to analyze the adsorption of chromium from aqueous solution. The results concluded that Freundlich isotherm captured the adsorption of Chromium better compared to Langmuir isotherm as the former have higher correlation regression coefficient.